Canadian 24-Hour Movement Guidelines for the Early Years (0–4 years): An Integration of Physical Activity, Sedentary Behaviour, and Sleep - Tremblay, Mark S; Chaput, Jean-Philippe; Adamo, Kristi B; Aubert, Salomé; Barnes, Joel D; Choquette, Louise; Duggan, Mary; Faulkner, Guy; Goldfield, Gary S; Gray, Casey E; Gruber, Reut; Janson, Katherine; et al. (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background The Canadian Society for Exercise Physiology convened representatives of national organizations, research experts, methodologists, stakeholders, and end-users who followed rigorous and transparent guideline development procedures to create the Canadian 24-Hour Movement Guidelines for the Early Years (0–4 years): An Integration of Physical Activity, Sedentary Behaviour, and Sleep. These novel guidelines for children of the early years embrace the natural and intuitive integration of movement behaviours across the whole day (24-h period). Methods The development process was guided by the Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument. Four systematic reviews (physical activity, sedentary behaviour, sleep, combined behaviours) examining the relationships within and among movement behaviours and several health indicators were completed and interpreted by a Guideline Development Panel. The systematic reviews that were conducted to inform the development of the guidelines, and the framework that was applied to develop the recommendations, followed the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Complementary compositional analyses were performed using data from the Canadian Health Measures Survey to examine the relationships between movement behaviours and indicators of adiposity. A review of the evidence on the cost effectiveness and resource use associated with the implementation of the proposed guidelines was also undertaken. A stakeholder survey (n = 546), 10 key informant interviews, and 14 focus groups (n = 92 participants) were completed to gather feedback on draft guidelines and their dissemination. Results The guidelines provide evidence-informed recommendations as to the combinations of light-, moderate- and vigorous-intensity physical activity, sedentary behaviours, and sleep that infants (<1 year), toddlers (1–2 years) and preschoolers (3–4 years) should achieve for a healthy day (24 h). Proactive dissemination, promotion, implementation, and evaluation plans were prepared to optimize uptake and activation of the new guidelines. Conclusions These guidelines represent a sensible evolution of public health guidelines whereby optimal health is framed within the balance of movement behaviours across the whole day, while respecting preferences of end-users. Future research should consider the integrated relationships among movement behaviours, and similar integrated guidelines for other age groups should be developed.